Responsiveness and seasonal variation of a 12×25-m swimming test - Mitchell, L. J. G.; Rattray, B.; Wu, P.; Saunders, P. U.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Critical speed (CS) and supra-CS distance capacity (D') are useful metrics for monitoring changes in swimmers' physiological and performance capacities. However, the utility of these metrics across a season has not been systematically evaluated in high-level swimmers. Methods: A total of 27 swimmers (mean [SD]: 18 females, age = 19.1 [2.9] y, and 9 males, age = 19.5 [1.9] y) completed the 12 × 25-m swimming test multiple times (4 [3] tests/swimmer) across a 2-y period. Season-best times in all distances for the test stroke were sourced from publicly available databases. Swimmers' distance speciality was determined as the event with the time closest to world record. Four metrics were calculated from the 12 × 25-m test: CS, D', peak speed, and drop-off %. Results: Guyatt responsiveness index values were calculated to ascertain the practically relevant sensitivity of each 12 × 25-m metric: CS = 1.5, peak speed = 2.3, D' = 2.1, and drop-off % = 2.6. These values are modified effect sizes; all are large effects. Bayesian mixed modeling showed substantial between-subjects differences between genders and strokes for each variable but minimal within-subject changes across the season. Drop-off % was lower in 200-m swimmers (14.0% [3.3%]) than in 100-m swimmers (18.1% [4.1%], P = .003, effect size = 1.10). Conclusions: The 12 × 25-m test is best suited to differentiating between swimmers of different strokes and events. Further development is needed to improve its utility in quantifying meaningful changes over a season for individual swimmers.